2021
DOI: 10.3390/app11188402
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bathing Therapeutic Approach for Diabetic Foot Ulcers

Abstract: Ineffective healing and treatment of foot ulcers can lead to an infection and gangrene of the wound area that ultimately results in the loss of the limb. The incidence of foot ulcers is higher in patients with diabetes, peripheral vascular disease and kidney disease. Accordingly, this study was undertaken to assess the ability of foot bathing in CO2-enriched water to heal foot ulcers. The design was a double-blinded, randomized, placebo-controlled study. Patients with at least one foot ulcer were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In view of higher incidence of ulcers in patients with diabetes, bathing in CO 2 -enriched water has been reported to accelerate healing of foot ulcers [28]. We have also observed that 4 weeks of CO 2 therapy augmented the blood flow and angiogenesis in the skeletal muscle of 6 weeks diabetic-ischemic hind limb of rats [25].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…In view of higher incidence of ulcers in patients with diabetes, bathing in CO 2 -enriched water has been reported to accelerate healing of foot ulcers [28]. We have also observed that 4 weeks of CO 2 therapy augmented the blood flow and angiogenesis in the skeletal muscle of 6 weeks diabetic-ischemic hind limb of rats [25].…”
Section: Introductionsupporting
confidence: 55%
“…Since diabetes is associated with several risk factors including hypertension for inducing vascular complications, it would be valuable to examine the effectiveness of CO 2 waterbath therapy by employing diabetic-hypertensive animals. Nonetheless, a preliminary study in diabetic patients with foot ulcers has shown some promising results with CO 2 water-bath treatment [28], and it is hoped that a large clinical trial will be undertaken to establish beneficial effects of CO 2 therapy for the treatment of vascular complications in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation